2015
DOI: 10.3390/ijerph120504889
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Indoor Air Quality before, during and after Unrestricted Use of E-Cigarettes in a Small Room

Abstract: Airborne chemicals in the indoor environment arise from a wide variety of sources such as burning fuels and cooking, construction materials and furniture, environmental tobacco smoke as well as outdoor sources. To understand the contribution of exhaled e-cigarette aerosol to the pre-existing chemicals in the ambient air, an indoor air quality study was conducted to measure volatile organic compounds (including nicotine and low molecular weight carbonyls), polycyclic aromatic hydrocarbons, tobacco-specific nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
1
41
1
1
Order By: Relevance
“…14,15,18,19,[22][23][24][25]27,29 Two studies did not comment on the passive exposure risk 16,17 , and four concluded that their investigation showed no risk to bystanders. 20,21,26,28 It is noted that those studies undertaken by tobacco employees or funded by the National Vapers Club concluded no apparent risk from ECs to bystanders. Those who did not declare a conflict of interest were more likely to draw conclusions that were more precautionary and/or suggested a potential risk from passive exposure to ECs, highlighting potential biases in the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,15,18,19,[22][23][24][25]27,29 Two studies did not comment on the passive exposure risk 16,17 , and four concluded that their investigation showed no risk to bystanders. 20,21,26,28 It is noted that those studies undertaken by tobacco employees or funded by the National Vapers Club concluded no apparent risk from ECs to bystanders. Those who did not declare a conflict of interest were more likely to draw conclusions that were more precautionary and/or suggested a potential risk from passive exposure to ECs, highlighting potential biases in the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…When examining the absolute impact from passive exposure to EC vapour -that is, comparing EC vapour with background levels -EC vapour contains elevated levels of nicotine 19,20,24 , PM 19,22,24,25,29 , glycerine 20,24 , propylene glycol 21,24 , formaldehyde and acetaldehyde 21 , PAHs and metals. 24 These studies demonstrate that EC vapours can contain harmful chemicals and have an impact on indoor air quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schober et al (2014) [36] fanden in einem Büroraum unter üblichen Lüftungsbedingungen während 6 jeweils zweistündiger Rauchsitzungen PG-Gehalte von 110-395 µg/m³; ohne das Rauchen von E-Zigaretten lagen die PG-Gehalte unter 0,04 µg/m³. In einem kleinen Besprechungsraum, in dem 3 Personen über 165 Minuten E-Zigaretten dampften, wurde in diesem Zeitraum ein Gehalt von 204 µg PG/m³ in der Innenraumluft gemessen, während vor der Rauchsitzung nur Konzentrationen von <0,5 µg/m³ beobachtet wurden [31]. Beim Verdampfen von PG aus E-Zigaretten liegt PG als Aerosol in der Innenraumluft vor, wobei das Maximum von Partikeln Durchmesser zwischen 20-30 nm aufweist [36,37].…”
Section: Bekanntmachung Des Umweltbundesamtesunclassified